The relation between earnings and cash flows - Dechow, Patricia M.; Kothari, S.P.; L. Watts, Ross (Journal of Accounting and Economics, 1998)
A model of earnings, cash flows and accruals is developed assuming a random walk sales process, variable and fixed costs, and that the only accruals are accounts receivable and payable, and inventory. The model implies earnings better predict future operating cash flows than current operating cash flows and the difference varies with the operating cash cycle. Also, the model is used to predict serial and cross-correlations of each firm's series. The implications and predictions are tested on a 1337 firm sample over 1963–1992. Both earnings and cash flow forecast implications and correlation predictions are generally consistent with the data.